Analysis of the secondary heating system of Södra Cell Mönsterås - Nihlmark, Fredrik; Mahmoud, Mohammed (My University, 2017)
As one of the means to tackle global warming, the European Union established the 2012 Energy Efficiency Directive. As a part of fulfilling this directive, Sweden implemented the law about energy auditing for large enterprises, which aims at promoting possible energy efficiency targets. The energy audit should map the amount of energy supplied and consumed required to run the business and propose measures for the enterprise to reduce energy consumption and thereby increase their energy efficiency. The pulp and paper industry accounted for roughly 17 % of Sweden’s total energy consumption during 2016, which indicates the importance of energy efficiency improvements within this industry. A huge player within the Swedish pulp and paper industry is Södra. This project was carried out at Södra’s oldest and biggest pulp mill Södra Cell Mönsterås. One way to improve its energy efficiency is by better utilizing the excess heat from the pulping process in its secondary heating system. However, Södra Cell Mönsterås main focus to produce and sell high-quality pulp has led to that the design and function of their secondary heating system has not been prioritised, resulting in lack of knowledge about their system with regards to potential energy savings, sizes of heat exchangers, consumers/producers of hot and warm water and operating data, such as temperatures and flows. This is particularly true for the digester section. Consequently the aim of this project has been to increase the knowledge of the design and function of the secondary heating system of Södra Cell Mönsterås, with special attention to the digester section and to collect and evaluate data to support future energy efficiency studies. By studying piping and instrumentation diagrams and by collecting data through Södra Cell Mönsterås process monitoring control system (INFOPLAN), engineering estimations and measurements, the design and function of the secondary heating system of Södra Cell Mönsterås for the entire mill and for the digester section could be mapped. This was also done for the steam system and the internal and external heating networks. All the gathered data for these systems has been evaluated in terms of variations, data availability, data sources and extraction period and presented in graphs and tables. All this together increases the knowledge of the design and function of the presented systems and serves as a support for future energy efficiency studies or energy audits. Also, it serves as a basis for the carried out pinch analysis in order to identify energy targets. v From the pinch analysis it was found that, in theory, there is a potential to save 79 MW of primary energy. The pinch analysis also showed a possibility to produce 38.3 MW of hot water at 114 C in the digester section. Since the current hot water demand is 20.9 MW, there is a theoretical possibility to achieve energy savings of 17.4 MW at various parts of the mill. However, it must be investigated further in future work how these energy savings can be achieved. To provide more accurate energy targets and to be able to come with suggestions on how to achieve these energy targets, the pinch analysis most be improved by identifying more individual streams. To further facilitate future energy efficiency projects, it is also suggested that current piping and instrumentation diagrams are continuously updated and more stationary measuring equipment for temperatures and flows are installed, especially in the digester section. Further, the possibility to introduce another water tank level should be investigated along with the possibility to replace low-pressure steam by hot water at 114 C at some locations. Lastly, additional future work would be to investigate the practical feasibility and economical profitability of constructing an improved energy recovery heat exchanger network and introducing flue gas cooling as a measure for achieving primary energy savings.
Keywords: Energiteknik; Hållbar utveckling; Energi; Energy Engineering; Sustainable Development; Energy